Pengaruh Pemberian Buah Nanas Terhadap Kadar Asam Urat di Kelurahan Batulubang Lembeh Selatan - Indria Putri Utina; Agust A. Laya; Nurlela Hi. Baco (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2023)
Background: Increased of uric acid levels can be caused other disorders in the human body such as a feeling of aches and pains in the joint area and is often along with extreme pain for the sufferer. This disease is better known as gout (Andry, 2021 ). Objective: This study aims to find out the effectiveness of consumption the pineapple fruit on reducing uric acid levels in the Batu Lubang Lembeh Selatan Village. This research uses a Pre-Experimental method with a One Group Pre-Post Test Design approach. The samples in this study were 12 early adult men who with having gout in Batu Lubang Lembeh Selatan Village, using an accidental sample. The data collected using observation sheets and analyzed using the non-parametric Wilcoxon test using SPSS. The results of the research showed the conditions of uric acid sufferers before and after consumption pineapple analysis the value of 0.003, there was a significant effect between giving pineapple fruit on reducing uric acid levels in the Batu Lubang Lembeh Selatan sub-district. The conclusion in this study there were an effect of giving pineapple on reducing uric acid levels in Batu Lubang Lembeh Selatan Village. Based on the research results, it is recommended the Respondents be expected to frequently consume pineapple so that uric acid levels can decrease till the normal limits.